Physiological determinants of urine and plasma myomiRNAs in recreational, middle-age athletes - Danese, Elisa; Benati, Marco; Sanchis-Gomar, Fabian; Tarperi, Cantor; Salvagno, Gian Luca; Paviati, Elisa; Montagnana, Martina; Schena, Federico; Lippi, Giuseppe (Journal of Laboratory and Precision Medicine, 2017)
Background: The clinical use of micro RNAs (miRNAs) in the diagnostics of muscle injury should take into account the possible influence of many variables such as genetic factors, age, sex, ethnic origin, body and tissue composition as well as physical fitness. Therefore, the present study was designed to identify potential physiological determinants of miRNA 133-a and miRNA 206 in a population of recreational, middle-aged athletes. Methods: The study group consisted of 28 healthy, middle-aged recreational athletes (11 women and 17 men) regularly engaged in endurance running. Resting urine and blood samples were collected for assessing plasma and urine miRNA 133-a and miRNA 206, and for serum measurement of creatine kinase (CK) and cardiac troponin T (cTnT). Results: In univariate analysis, no physiological or laboratory parameter was associated with the plasma concentration of both miRNA 133-a and miRNA 206. The urine concentration of miRNA 133-a was associated with sex and body mass index (BMI), whereas the urine concentration of miRNA 206 was associated with sex and serum cTnT. In multivariate logistic regression analysis, the urine concentration of both miRNAs remained associated only with sex. The urine miRNA133-a and miRNA 206 values were found to be 3.0 and 1.9 folds higher in female than in male athletes, respectively. The percent overlap between the female and male populations of athletes was 27% for urine miRNA 133-a and 41% for urine miRNA 206. Conclusions: The results of this study demonstrate that the plasma concentration of miRNA 133-a and 206 is virtually independent from the most common physiological variables, whereas the urine reference values of these two myomiRNAs should be partitioned by sex.